2023
DOI: 10.3389/fpls.2022.1067076
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolic regulatory network characterization of drought responses in tobacco

Abstract: Drought stress usually causes huge economic losses for tobacco industries. Drought stress exhibits multifaceted impacts on tobacco systems through inducing changes at different levels, such as physiological and chemical changes, changes of gene transcription and metabolic changes. Understanding how plants respond and adapt to drought stress helps generate engineered plants with enhanced drought resistance. In this study, we conducted multiple time point-related physiological, biochemical,transcriptomic and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…In contrast, genes and metabolites related to sugar metabolism were less changed in ‘Pacific Early’, indicating that ‘Pacific Early’ failed to produce more osmoregulatory substances to resist drought stress. The TCA cycle is an important component of plant energy metabolism [ 21 , 23 , 47 ]. In this study, in ‘Jilv3’ under drought stress, the TCA cycle was enhanced by the upregulation of related DEGs, including SDH , CS , SDH , and IDH , which could efficiently improve the utilization of malic acid, citric acid, and succinic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, genes and metabolites related to sugar metabolism were less changed in ‘Pacific Early’, indicating that ‘Pacific Early’ failed to produce more osmoregulatory substances to resist drought stress. The TCA cycle is an important component of plant energy metabolism [ 21 , 23 , 47 ]. In this study, in ‘Jilv3’ under drought stress, the TCA cycle was enhanced by the upregulation of related DEGs, including SDH , CS , SDH , and IDH , which could efficiently improve the utilization of malic acid, citric acid, and succinic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Under drought stress, metabolic processes, such as the citrate cycle (TCA cycle), glucose metabolism, and glycolysis/gluconeogenesis, change to different degrees. These metabolisms correspond closely to drought resistance [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the regulators of the BCR signaling pathway is miR‐150. Several studies have shown that this miRNA adjusts the level of the FOXP1 transcription factor in CLL cells [61‐63]. FOXP1 is an essential factor in the BCR, NF‐κB, and Wnt signaling [64, 65] and its overexpression is associated with several B lymphocyte malignancies and adverse outcomes in the corresponding patients [64, 66].…”
Section: Introductionmentioning
confidence: 99%
“…The ADH gene family plays vital roles in plant growth and development, as well as in responding to various stresses such as low temperature [ 8 ], drought [ 9 ], salt [ 10 ], mechanical damage [ 11 ], and the exogenous hormone abscisic acid [ 12 ]. In Panax ginseng , the positive response of PgADHs to abiotic stresses, including ABA, SA, and JA treatment, suggests that PgADHs are genuinely involved in these hormone-related stress responses [ 13 ].…”
Section: Introductionmentioning
confidence: 99%